DNA Aptamers Targeting BcSOD1: A Novel Strategy forControlling Botrytis cinerea in Sustainable Agriculture - López-Laguna, Alba; Polonio Escalona, Alvaro Acisclo; Jiménez Castro, Lucía; Morales, Yandira; Vielba-Fernández, Alejandra; Martín Palma, María Elena; González Muñoz, Víctor Manuel; De-Vicente-Moreno, Antonio; Pérez-García, Alejandro; Fernández-Ortuño, Dolores (Wiley, 2025)
Botrytis cinerea, the necrotrophic fungus responsible for grey mould disease, is a major threat to global crop production. Controlstrategies mainly rely on chemical fungicides, but resistance development limits their long-term effectiveness. This study intro-duces, for the first time in crop protection, the use of DNA aptamers as a novel and sustainable strategy. Aptamers are short, single-stranded DNA molecules that bind specific targets with high affinity, acting like ‘chemical antibodies’. Using SELEX technology,two aptamers, SOD9.14F and SOD9.26F, were designed to target BcSOD1, a superoxide dismutase enzyme essential for fungalvirulence and ROS detoxification. Molecular modelling predicted that both aptamers bind within BcSOD1's catalytic pocket.Both aptamers inhibited BcSOD1 enzymatic activity (97.5%) and reduced germination (67%), fungal biomass (58%) and lesionformation (42%) in B. cinerea-infected tomato leaves (Solanum lycopersicum) and apple fruits (Malus domestica). Fluorescencemicroscopy confirmed aptamer binding to conidia surfaces. No antifungal effect was observed in the ΔBcsod1 mutant or withthe non-structured control aptamer Ap.AGA, supporting target specificity. RNA-Seq analysis revealed that SOD9.26F inter-fered with fungal oxidative stress responses and metabolism. Additionally, aptamer application primed tomato plants, activatingdefence-related gene expression. Interestingly, Ap.AGA aptamer triggered partial priming, suggesting a broader DNA-inducedeffect. These findings validate BcSOD1 as an antifungal target and highlight aptamers as dual-action agents: impairing fungaldevelopment and enhancing plant immunity. This study positions DNA aptamers as specific, effective and sustainable tools forintegrated management of grey mould in agriculture.
Keywords: Control biológico; Biotecnología agrícola; Aptamer; Biofungicide; Botrytis cinerea; Control; Reactive oxygen species; Superoxide dismutase